Waters of Brazil : strategic analysis - Bicudo, Carlos E. de; Tundisi, J. G.; Scheuenstuhl, Marcos C. Barnsley (Springer, 2017)
This book is a product of Brazilian Academy of Sciences Study Group about water issue. The water cycle was addressed based on an integrated point of view, aiming at joining technological and ecological solutions and integrating quantitative and qualitative aspects of this important environmental asset. Issues such as the water resources management and irrigated agriculture, water and health, water and economy, conservation and reuse as management tools, water in the Brazilian semi arid, water in Amazon, urbanization and water resources, education for the sustainability of water resources, groundwater, availability, pollution and eutrophication of water and science, technology and innovation are of the utmost importance for this exact moment in Brazil, and particularly to the State of Sao Paulo. Addressing these issues will undoubtedly contribute towards a sustainable management of water resources trough the coordinated work of different fields of science, progressing a systemic view about water, that would then finally allow management professionals the possibility of an integral action in anticipating problems and thus anticipate solutions.- Resumé vydavatel
Keywords: voda -- Brazílie; zásobování vodou -- Brazílie; kvalita vody -- Brazílie; water -- Brasil; water supply -- Brasil; water quality -- Brasil; elektronické knihy; sborníky; electronic books; papers of several authors